Chapter Between the Mediterranean and the North Sea: Networks of Men and Ports (14th-15th Centuries) - Orlandi, Angela (Atti delle «Settimane di Studi» e altri Convegni, 2019)
This essay examines how the various processes of economic integration brought about by commercial exchanges were influenced by networks of merchants, by the different functions and capacities of ports, and by the various locations of routes established between the Mediterranean, the Atlantic and the North Sea. The ports, the routes and ships, and the mentality and culture of the economic operators represent the three main themes of this study; it aims to observe and compare maritime environments which were completely different from one another, especially in terms of the size of the ports and the importance of the commercial itineraries based on them.